(3LGeY CSQGQ GdWHs - (3RgQ Hf YHO Gdedc Hf eMeO Hf RgQ GdGTHjdj, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3bGd GdhRjQ CHhGdYdGA Hf RgQ QMeg Gddg(B: (3CYde faYfG Gddg hEjGc Gf LSe GdEfSGf BNQ GdJQcjH , dGjJQcH efg ZjQ EfSGf s
(3BNQgG (B:s
(3jUfY ef GdLejY ZHGQ hjTQH HeGA aGJQ , aEfg fGaY Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B268s
(3GfXQ agQS GdeNWhWGJ GdYQHjI HGdNRGfI GdYGeI (B-(3GdQHGW (B336/2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B73 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs